Critical review of Islamic economics - literature and human resource: are we moving together? - Haneef, Mohamed Aslam (2017)
Islamic Economics is now at least 40 years old (modern economics is 240 years old) No doubt that 20thCentury CE-resurgence of Islam in all dimensions, including intellectual with IEF at the forefront But has IEF genuinely contributed to the ummah? Theory and practice? This paper surveys literature for the last 40 years-10 ICIEFs since 1976 This paper looks at the IEF academics (Malaysia as represented in Malaysia Islamic Finance Education Report 2016) This paper investigates whether there is misalignment of resources between curriculum and our academics Some Issues and Suggestions